Atsiminimai apie J. Tumą-Vaižgantą - Vaitiekūnienė, Aldona (Literatūra, 1970)
In this article some reminiscences on Lithuanian writer J. Tumas-Vaižgantas are presented by his relatives and acquaintances. The memoir material will throw some light on a better knowledge of the writer's personality, especially some moments in his biography, the first years of his life activities. The present material includes some facts on the prototypes depicted in some Vaižgantas's works (“Uncles and Aunts,” “The Degenerate”), and gives some explanation of his works. The present material is collected by the students of Lithuanian at the Vilnius Pedagogical Institute, and it is kept in the Institute, in the Lithuanian language and literature chair.